Responses of Madrasah to Social Change: A Study on Madrasah Aliyah in Bengkulu City - Samsudin, Samsudin (Madania: Jurnal Kajian Keislaman, 2020)
Madrasah Aliyah is an Islamic educational institution that combines the teaching of religious sciences and general science. Madrasah Aliyah is an agent of change and at the same time Madrasah Aliyah as an object of social change. The problem of this research is how Madrasah Aliyah responds to the process of change that occurs in the community. The purpose of this study is to describe the forms of activities undertaken by Madrasah Aliyah in response to social changes that occur in Bengkulu. By using descriptive qualitative methods with a sociological approach, research data were obtained through interview, observation and documentation techniques. Subsequent research data were analyzed using Miles and Huberman's perspective flow model. The results of the study are that the response of Madrasah Aliyah to social change, including improving various functions of the madrasah, improving the function of transformation and adaptability, strengthening the formation of religious character and social control, encouraging becoming an inventor / innovator, increasing the miniature function of family religion, values education universal, and strengthening the synergy of the tri-education center (education in the family (informal education), education in schools (formal education), and education in the community (non formal education). Madrasah Aliyah merupakan lembaga pendidikan Islam yang memadukan pengajaran ilmu-ilmu agama dan ilmu pengetahuan umum. Madrasah Aliyah merupakan agen pencipta perubahan dan dalam waktu yang bersamaan Madrasah Aliyah sebagai objek perubahan sosial. Permasalahan penelitian ini adalah bagaimana Madrasah Aliyah merespon proses perubahan yang terjadi di masyarakat. Tujuan penelitian ini adalah mendeskripsikan bentuk-bentuk kegiatan yang dilakukan Madrasah Aliyah sebagai respon atas perubahan sosial yang terjadi di Bengkulu. Dengan menggunakan metode kualitatif deskriptif dengan pendekatan sosiologis, data penelitian diperoleh melalui teknik wawancara, observasi dan dokumentasi. Data penelitian selanjutnya dianalisis dengan menggunakan model alir perspektif Miles dan Huberman. Hasil penelitian, bahwa respon Madrasah Aliyah terhadap perubahan sosial, di antaranya meningkatkan berbagai fungsi madrasah, di antaranya  meningkatkan fungsi transformasi dan adaptabilitas, penguatan pembentukan karakter keagamaan dan kontrol sosial, mendorong menjadi inventor/innovator, meningkatkan fungsi miniatur keagamaan keluarga, pendidikan nilai-nilai universal, dan penguatan sinergitas tri pusat pendidikan